Insulating adhesive layer and battery cell

By using specific insulating adhesive layer and multi-layer adhesive film structures in lithium-ion batteries, combined with metal sheet design, effective pressure relief at high temperatures is achieved, battery safety problems are solved, and safety performance and pressure relief functions are improved.

CN119220186APending Publication Date: 2024-12-31ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411352902.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Lithium-ion batteries may cause a sharp rise in the battery cell temperature during high temperatures or short circuits, causing safety accidents such as fire and explosions. The existing sealing mechanism is difficult to effectively relieve pressure, affecting the safety performance of the battery.

Method used

The insulating adhesive layer with specific performance has the function of opening pressure relief at a specific temperature. Combined with the multi-layer film structure and the design of the metal sheet, it ensures both sealing and pressure relief function.

Benefits of technology

It improves the safety performance of the battery, avoids fire and explosion accidents caused by bloating, and maintains the sealing of the battery under normal use, enhancing the sensitivity and reliability of the pressure relief function.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220186A_ABST
    Figure CN119220186A_ABST
Patent Text Reader

Abstract

The invention provides an insulating adhesive layer, in an XRD (X-Ray Diffraction) pattern of the insulating adhesive layer, a first diffraction peak exists at the 2 theta angle position of 9-12 degrees, a second diffraction peak exists at the 2 theta angle position of 13-15 degrees, and the ratio of the peak intensity of the first diffraction peak to the peak intensity of the second diffraction peak is (0.5-5): 1. In the invention, by controlling the peak intensity ratio of diffraction peaks existing in the range of 2 theta angle 9-12 degrees and 13-15 degrees in the XRD pattern of the insulating adhesive layer to be (0.5-5): 1, the product performance can have good rigidity and transparency, the transparency, impact strength and low-temperature impact resistance of the material are improved, meanwhile, the overall heat resistance of the material is reduced, and the service life of the material is prolonged. And in the battery cell, the temperature of the pressure relief opening of the material is reduced, so that the pressure relief function and the sealing function are well realized. According to the insulating adhesive layer provided by the invention, the sealing performance of the battery cell in normal use can be ensured, and the battery cell can realize pressure relief at a specific temperature, so that safety accidents such as fire and explosion caused by gas expansion of the battery cell are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a lithium ion battery sealing mechanism and a lithium ion battery. Background Art

[0002] With the rapid development of new energy technologies, lithium-ion batteries are widely used in various portable electronic devices (mobile phones, digital cameras, etc.) as well as electric vehicles and power tools due to their advantages such as high energy density, high voltage and long cycle times.

[0003] In recent years, as the requirements for fast charging and capacity of battery cells have continued to increase, battery cells will continue to generate heat under high temperature conditions or during a short circuit, and the internal temperature of the battery cells will rise sharply. Fire and explosion of the battery cells may cause safety problems and cause irreparable losses. Therefore, to prevent thermal runaway of the battery cells, higher requirements are placed on the safety performance of the battery cells.

[0004] Therefore, a sealing mechanism with both good pressure relief and sealing performance is the key to ensuring battery safety. Summary of the invention

[0005] At present, steel shell battery cells are mainly composed of positive electrode components, negative electrode components, isolation membranes, electrolytes, shell components and sealing mechanisms. The steel shell and the sealing mechanism are laser welded to form a closed environment for the battery cell to isolate moisture and air. When the battery cell encounters a violent impact during use or is improperly used during charging and discharging, the battery cell temperature rises sharply, the electrolyte decomposes under high temperature, and the CEI / SEI further decomposes, causing the positive and negative electrode side reactions to intensify, generating high-temperature and high-pressure gases inside. If the above gases cannot be discharged in time, the battery cell may cause fires and explosions due to flatulence, causing safety accidents.

[0006] In view of this, the technical problem to be solved by the present invention is to provide an insulating glue layer and a battery cell. The present invention uses an insulating glue with specific properties applied to the sealing mechanism of the battery, so that the sealing mechanism of the battery cell can open at a specific temperature while ensuring the sealing performance, thereby achieving pressure relief and improving the safety performance of the battery.

[0007] The present invention provides an insulating adhesive layer, in which an XRD spectrum of the insulating adhesive layer has a first diffraction peak at a 2θ angle position of 9 to 12°, a second diffraction peak at a 2θ angle position of 13 to 15°, and a ratio of the peak intensity of the first diffraction peak to the second diffraction peak is (0.5 to 5):1.

[0008] Preferably, the half-peak width of the first diffraction peak is 0.2-2°.

[0009] Preferably, in the infrared absorption spectrum of the insulating adhesive layer, at a wave number 1 / λ of 1500 to 1300 cm -1The interval includes a first absorption peak and a second absorption peak, and the wave number 1 / λ of the first absorption peak is 1400-1300cm -1 The wave number 1 / λ of the second absorption peak is 1500-1430 cm -1 The ratio of the absorption intensity of the first absorption peak to that of the second absorption peak is 1:(0.5-2), preferably 1:(0.6-1.5).

[0010] Preferably, the insulating adhesive layer is compressed with a force of 0.1N in a vertical direction of the insulating adhesive layer, and the temperature of the insulating adhesive layer is increased from room temperature at a rate of 10°C / min. Within the range of 40 to 100°C, the thermal compression deformation of the insulating adhesive layer is 2% to 30%, preferably 5% to 20%.

[0011] Preferably, the melting point of the insulating adhesive layer is 70 to 160°C;

[0012] And / or the thickness of the insulating rubber layer is 0.02 mm to 0.15 mm.

[0013] Preferably, the insulating adhesive layer comprises a polyolefin compound;

[0014] Preferably, the polyolefin compound includes propylene polymer and butene polymer;

[0015] Preferably, the propylene polymer includes one or more of polypropylene, polypropylene chloride, polyacrylic acid, polyacrylate, and polyacrylonitrile;

[0016] The butene polymer includes one or more of polybutene, polychloroprene, and polybutene acid.

[0017] Preferably, the insulating adhesive layer includes one or more adhesive films.

[0018] Preferably, the insulating adhesive layer comprises an a-layer adhesive film, a c-layer adhesive film and a b-layer adhesive film which are arranged in sequence, the total thickness of the insulating adhesive layer is 0.02-0.12 mm, and the thickness ratios of the a-layer adhesive film, the c-layer adhesive film and the b-layer adhesive film are (1-3):(1-3):(1-3) in sequence;

[0019] Preferably, the a-layer adhesive film comprises a butene polymer, has a thickness of 0.005 to 0.04 mm, and a melting point of 70 to 120° C.;

[0020] The b-layer adhesive film includes a butene polymer, has a thickness of 0.005 to 0.04 mm, and a melting point of 70 to 120°C;

[0021] The c-layer adhesive film includes an propylene polymer, has a thickness of 0.005 to 0.04 mm, and a melting point of 130 to 160°C;

[0022] Preferably, the melting point of the c-layer adhesive film is 20-70° C. higher than that of the a-layer adhesive film, and the melting point of the c-layer adhesive film is 20-70° C. higher than that of the b-layer adhesive film.

[0023] Preferably, in a DSC test, the insulating adhesive layer has a crystallization peak at 30-130°C;

[0024] Preferably, the insulating adhesive layer comprises a first crystallization peak and a second crystallization peak at 30-130°C, the crystallization temperature of the first crystallization peak is 90-120°C, and the crystallization temperature of the second crystallization peak is 30-60°C.

[0025] Preferably, under nitrogen atmosphere conditions, the insulating adhesive layer has a heating rate of 10°C / min in a TG test, and when the temperature reaches 400°C, the weight loss rate of the insulating adhesive layer is less than 10%; when the temperature reaches 600°C, the weight loss rate of the insulating adhesive layer is greater than 99%.

[0026] The present invention also provides a battery cell, comprising:

[0027] A shell body, wherein the shell body is provided with a liquid injection hole;

[0028] A sealing structure, wherein the sealing structure covers the injection hole, the sealing structure comprises a first metal sheet, a second metal sheet and an insulating adhesive layer arranged between the first metal sheet and the second metal sheet, and the insulating adhesive layer comprises the above-mentioned insulating adhesive layer.

[0029] Preferably, the insulating adhesive layer comprises an a-layer adhesive film, a c-layer adhesive film and a b-layer adhesive film arranged in sequence, the a-layer adhesive film is connected to the first metal sheet, and the surface of the a-layer adhesive film close to the first metal sheet comprises C element and O element, wherein the mass content ratio of C element to O element is between 95:5 and 99.8:0.2; and / or

[0030] The b-layer adhesive film is connected to the second metal sheet, and the b-layer adhesive film and the surface close to the second metal sheet include C element and O element, wherein the mass content ratio of C element to O element is between 95:5 and 99.8:0.2.

[0031] Preferably, the material of the first metal sheet includes one or more of nickel, nickel alloy, copper, copper-plated nickel, aluminum and aluminum alloy;

[0032] The material of the second metal sheet includes one or more of nickel, nickel alloy, copper, copper-plated nickel, aluminum and aluminum alloy;

[0033] Preferably, the copper-nickel plating comprises nickel and a copper-containing plating layer arranged on the surface of the nickel, and the thickness of the copper-containing plating layer is 0.01-0.15 μm.

[0034] Preferably, the thickness of the first metal sheet is 0.05-0.12 mm;

[0035] The thickness ratio of the first metal sheet to the second metal sheet is 1:(0.5-3);

[0036] The thickness ratio of the first metal sheet to the insulating adhesive layer is (1-3):1.

[0037] Preferably, the first metal sheet is connected to the housing, and the first metal sheet is provided with a first pressure relief hole;

[0038] The insulating rubber layer is provided with a second pressure relief hole.

[0039] Preferably, the area of ​​the first pressure relief hole is smaller than the area of ​​the liquid injection hole;

[0040] The area of ​​the second pressure relief hole is smaller than that of the first pressure relief hole, and along the vertical projection direction, the first pressure relief hole completely covers the second pressure relief hole;

[0041] Preferably, the area of ​​the first pressure relief hole is 0.2-5 mm 2 The area of ​​the second pressure relief hole is 0.03~4mm 2 The connection area between the insulating adhesive layer and the first metal sheet is 1 to 20 mm 2 .

[0042] Preferably, the area of ​​one side of the second metal sheet connected to the insulating adhesive layer is smaller than the total area of ​​the insulating adhesive layer and the second pressure relief hole, and the area of ​​one side of the second metal sheet connected to the insulating adhesive layer is larger than the area of ​​the second pressure relief hole, and the second metal sheet covers the second pressure relief hole;

[0043] Preferably, the area of ​​the second metal sheet connected to the insulating adhesive layer is 2 to 30 mm 2 The bonding area between the second metal sheet and the insulating adhesive layer is 1 to 15 mm 2 .

[0044] Preferably, the insulating rubber layer is a ring with an inner diameter of 0.2 to 1.4 mm and an outer diameter of 1.5 to 5 mm.

[0045] Preferably, the battery cell comprises a shell, a shell cover, an electrode assembly and an electrolyte, the shell cover is arranged on the shell, and the electrode assembly is arranged in the shell;

[0046] The electrode assembly comprises a positive electrode sheet, a separator, and a negative electrode sheet stacked in layers;

[0047] Preferably, the housing is a steel shell.

[0048] Preferably, the electrode hole and the injection hole for setting the positive electrode of the electrode assembly are located on the same side wall of the shell;

[0049] Preferably, the battery cell further comprises a notch, and the notch is arranged on the surface of the shell cover.

[0050] Preferably, the shell includes a first side wall, the pole hole injection hole of the positive pole is arranged on the first side wall, the sealing structure covers the injection hole, one side of the first metal sheet of the sealing mechanism is connected to the first side wall, the side of the first metal sheet facing away from the shell is connected to the insulating rubber layer, and the side of the insulating rubber layer facing away from the first metal sheet is connected to the second metal sheet.

[0051] Compared with the prior art, the present invention provides an insulating adhesive layer; in the XRD spectrum of the insulating adhesive layer, there is a first diffraction peak at 9-12° and a second diffraction peak at 13-15°, and the ratio of the peak intensity of the first diffraction peak to the second diffraction peak is (0.5-5):1. In the present invention, by controlling the peak intensity ratio of the diffraction peaks existing in the 2θ angle range of 9-12° and 13-15° in the XRD spectrum of the insulating adhesive layer to be (0.5-5):1, the product performance can have good rigidity and transparency, the transparency, impact strength, and low-temperature impact resistance of the material are improved, and the overall heat resistance of the material is reduced, which is manifested in the temperature drop of the pressure relief opening of the material in the battery cell. This performance enables it to achieve the pressure relief function and sealing function extremely well. The insulating adhesive layer provided by the present invention can ensure the sealing of the battery cell under normal use, and can also enable the battery cell to achieve pressure relief at a specific temperature, avoiding safety accidents such as fire and explosion caused by flatulence of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 Schematic diagram of thermal compression test on insulating rubber layer; wherein 1 is a push rod, 2 is an insulating rubber layer, and 3 is a base.

[0053] Figure 2 A schematic diagram of the structure of the sealing mechanism provided by the present invention; wherein, 11-shell; 111-liquid injection hole; 21-first metal sheet; 22-second metal sheet; 23-insulating rubber layer; 211-first pressure relief hole; 231-second pressure relief hole;

[0054] Figure 3 A schematic diagram of the structure of a lithium-ion battery provided by the present invention; wherein 1-shell; 2-sealing mechanism; 3-liquid injection hole; 4-positive electrode assembly; 5-negative electrode assembly;

[0055] Figure 4 This is the XRD detection spectrum of the insulating adhesive layer prepared in Example 1, wherein 2321 and 2322 are diffraction peaks of polybutene, and 2323 and 2324 are diffraction peaks of polypropylene;

[0056] Figure 5 This is the infrared spectrum of the insulating adhesive layer prepared in Example 1;

[0057] Figure 6 A sealing mechanism testing mold provided by the present invention; wherein, 31 is a push rod, 32 is an upper mold, 321 is a third through hole, 33 is a lower mold, and 331 is a fourth through hole. DETAILED DESCRIPTION

[0058] The present invention provides an insulating adhesive layer, in which an XRD spectrum of the insulating adhesive layer has a first diffraction peak at a 2θ angle position of 9 to 12°, a second diffraction peak at a 2θ angle position of 13 to 15°, and a ratio of the peak intensity of the first diffraction peak to the second diffraction peak is (0.5 to 5):1.

[0059] In the present invention, the insulating adhesive layer comprises component A and component B, the component A comprises propylene polymer, and the component B comprises butene polymer.

[0060] Specifically, in the XRD spectrum of the insulating adhesive layer, a first diffraction peak exists at a 2θ angle position of 9 to 12°, and a third diffraction peak exists at a 2θ angle position of 18 to 22°. The first diffraction peak and the third diffraction peak are characteristic peaks of butene polymers.

[0061] In the XRD spectrum of the insulating rubber layer, a second diffraction peak exists at a 2θ angle position of 13-15°, and a fourth diffraction peak exists at a 2θ angle position of 16-18°. The second diffraction peak and the fourth diffraction peak are characteristic peaks of propylene polymers.

[0062] The XRD diffraction peak shows that the material of the insulating rubber layer contains butene polymers and propylene polymers. Butene polymers and propylene polymers have good sealing properties. They can isolate water vapor when used in sealing mechanisms. They are also beneficial for the insulating rubber to release pressure before the battery cell thermal runaway, thereby preventing the battery cell from catching fire and exploding.

[0063] Among them, the crystal structure of butene polymers is hexagonal. In the industrial production process, the melt of butene polymers is cooled and crystallized to obtain a metastable tetragonal crystal with a low nucleation barrier. The processed products will spontaneously undergo a solid-solid phase transition to obtain a stable hexagonal crystal when placed at room temperature. The melting point, strength, hardness and other mechanical properties of the hexagonal crystal material are significantly improved. Hexagonal butene polymers are not only beneficial to the impact resistance of the sealing mechanism, but also can meet the pressure relief function of the sealing mechanism at high temperatures. Hexagonal butene polymers can also improve the reliability of the sealing mechanism, ensuring that the battery cell does not swell or leak electrolyte during high temperature and high humidity and long-term use.

[0064] In the present invention, the ratio of the peak intensity of the first diffraction peak to the second diffraction peak is controlled to be (0.5-5):1, which can be 0.5:1, 0.6:1, 0.8:1, 1.0:1, 1.2:1, 1.4:1, 1.5:1, 1.6:1, 1.8:1, 2.0:1, 2.2:1, 2.4:1, 2.5:1, 2.6:1, 2.8:1, 3.0:1, 3.2:1, 3.4:1, 3.5:1, 3.6:1, 3.8:1, 4.0:1, 4.2:1, 4.4:1, 4.5:1, 4.6:1, 4.8:1, 5.0:1, or any value between (0.5-5):1.

[0065] The present invention controls the peak intensity ratio of the first diffraction peak to the second diffraction peak to be (0.5-5):1, so that the insulating adhesive layer has good rigidity and transparency. Since the third comonomer butene is added to the insulating adhesive layer, the order of the entire molecular chain is reduced, the crystallinity is reduced, and visible light can pass through. The transparency, impact strength, and low-temperature impact resistance of the material are all improved. At the same time, the overall heat resistance of the material is reduced, which is manifested in the temperature drop of the pressure relief opening of the material in the sealing mechanism. This performance enables it to achieve the pressure relief function and sealing function of the sealing mechanism very well. When the peak intensity ratio is <0.5:1, the content of butene polymer in the insulating adhesive layer is too low or the crystallinity is poor. The poor crystallinity will lead to the reduction of the impact strength and low-temperature impact resistance of the insulating adhesive. Too little butene polymer will lead to the reduction of the sensitivity of the insulating adhesive to temperature, and the sealing mechanism cannot fully exert the pressure relief function. When the peak intensity ratio is >5:1, the content of butene polymer in the insulating adhesive layer is too high or the crystallinity is high. The high degree of crystallinity will increase the overall heat resistance of the insulating adhesive and the pressure relief effect of the sealing mechanism is poor. Too much butene polymer will cause the heat resistance of the insulating rubber layer to deteriorate. Although it helps the sealing mechanism to achieve the pressure relief function, it will increase the risk of using the battery cell at higher temperatures.

[0066] Furthermore, the width of the half-peak width of the first diffraction peak is 0.2-2°, wherein the width of the half-peak width can measure the degree of crystallization of polybutene. When the width of the half-peak width of the first diffraction peak is 0.2-2°, it can not only have good resistance to electrolyte corrosion, but also be beneficial to the impact resistance of the sealing mechanism, improve the reliability of the sealing mechanism, and also be beneficial to the insulating glue at high temperature, reaching a molten state and achieving pressure relief. When the width of the half-peak width is >2°, the crystallinity of the butene polymer in the insulating glue layer is poor, and the poor crystallinity will lead to reduced impact strength and low-temperature impact resistance of the insulating glue. When the width of the half-peak width is <0.2°, the degree of crystallization of the butene polymer in the insulating glue layer is high, and the high degree of crystallinity will increase the overall heat resistance of the insulating glue, and the pressure relief effect of the sealing mechanism is poor, and the pressure relief function cannot be fully exerted.

[0067] In the present invention, in the infrared absorption spectrum of the insulating adhesive layer, at a wave number 1 / λ of 1500 to 1300 cm -1 The interval includes a first absorption peak and a second absorption peak, and the wave number 1 / λ of the first absorption peak is 1400-1300cm -1 The wave number 1 / λ of the second absorption peak is 1500-1430 cm -1 The ratio of the absorption intensity of the first absorption peak to the second absorption peak is 1:(0.5-2), which can be 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1.0, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2; or any value between 1:(0.5-2). Preferably, it is any value between 1:(0.6-1.5).

[0068] In the infrared absorption spectrum of the insulating adhesive layer, 1378 cm -1 The methyl group (—CH 3 ) symmetrical angle absorption, 1460cm -1 Methylene (—CH 2 —) symmetrical angle-dependent absorption, among which at 1460cm -1 There is also an asymmetric angle-variable absorption of methyl nearby, which usually appears as a shoulder peak of the symmetric angle-variable absorption of methylene. Polybutene and polypropylene have very similar chemical structures, both of which are composed of methyl and methylene, but the relative content of methyl and methylene contained in the two is different. When the methyl absorption peak / methylene absorption peak intensity ratio is between 1: (0.5 and 2), the insulating glue within this range can achieve pressure relief before the thermal runaway of the battery cell to prevent the battery cell from catching fire and exploding. Further preferably, the peak intensity ratio of the two is 1: (0.6 to 1.5), the melting point of butene polymers is lower and the temperature sensitivity is high. When the methyl absorption peak / methylene absorption peak intensity ratio is between 1: (0.6 to 1.5), not only can the insulating glue be hot-melted and pressure relieved before the thermal runaway of the battery cell to prevent the battery cell from catching fire and exploding. It is also beneficial to the sealing of the battery cell during long-term use.

[0069] In the present invention, it is necessary to control the thermal compression deformation of the insulating adhesive layer, wherein the thermal compression deformation is tested by a dynamic thermal analyzer. In the thermal compression deformation test of the insulating adhesive, the insulating adhesive layer is fixed on a base inside the test cavity, and a load of 0.1N is applied to the insulating adhesive layer by a push rod in the vertical direction of the insulating adhesive layer. As the temperature rises, the Vicat softening point of the insulating adhesive layer is reached. The insulating adhesive is compressed and deformed under a load of 0.1N, and the thermal compression deformation of the insulating adhesive layer at different temperatures is recorded. Under the condition of an initial room temperature of 25±5°C, the thickness m of the insulating adhesive is recorded. 0The mold cavity is heated at 10°C / min according to the set program, and the thickness of the insulating rubber layer is recorded as the temperature changes. X The value of the thickness change of the insulating adhesive layer can represent the thermal compression deformation of the insulating adhesive layer at different temperatures. Figure 1 , Figure 1 Schematic diagram of thermal compression test on insulating adhesive layer, wherein 1 is a push rod, 2 is an insulating adhesive layer, and 3 is a base.

[0070] The calculation formula is shown in Formula I:

[0071] Thermal compression deformation = (m 0 -m x ) / m 0 *100% Formula I

[0072] In the present invention, the insulating glue layer is compressed with a force of 0.1N in the vertical direction of the insulating glue layer, and the temperature of the insulating glue layer is increased from room temperature at 10°C / min. In the range of 40 to 100°C, the maximum thermal compression deformation of the insulating glue layer is 2% to 30%, which can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, preferably 5% to 20%.

[0073] When the ambient or cell temperature exceeds 100°C, side reactions begin to occur inside the shell to produce gas. When the shell is inflated to generate pressure, the insulating rubber layer will be compressed. When the maximum thermal compression deformation value of the insulating rubber layer in the range of 40-100°C is between 2% and 30%, the cell can be more sensitive to thermal runaway and cell pressure relief, and the reliability of the sealing mechanism can be higher. If the maximum thermal compression deformation is <2%, the opening of the insulating rubber is small when the cell is in thermal runaway, and the sensitivity of the cell to pressure relief is low. If the maximum thermal compression deformation is >30%, the electrolyte vaporization of the steel shell cell during high-temperature storage will generate pressure, reducing the reliability of the sealing mechanism.

[0074] Further preferably, the thermal compression deformation of the insulating adhesive layer is controlled within a range of 5% to 20%, which can further more accurately control the thermal runaway of the battery cell, further improve the pressure relief sensitivity of the sealing mechanism, and enhance reliability.

[0075] In the present invention, the material of the insulating adhesive layer includes polyolefin compounds;

[0076] Preferably, the material of the insulating adhesive layer includes component A and component B, the component A includes propylene polymer, and the component B includes butene polymer;

[0077] Wherein, the propylene polymer includes one or more of polypropylene, polypropylene chloride, polyacrylic acid, polyacrylate, and polyacrylonitrile;

[0078] The butene polymer includes one or more of polybutene, polychloroprene, and polybutene acid.

[0079] The insulating adhesive layer provided by the present invention can have good resistance to electrolyte corrosion, which is beneficial to the reliability of the sealing mechanism under long-term use, and the above-mentioned material has a good ability to isolate water vapor, so that the sealing mechanism can achieve a sealing function; it is also beneficial for the insulating adhesive to form a molten state before reaching the thermal runaway temperature of the battery cell to achieve pressure relief.

[0080] In the present invention, the melting point of the insulating adhesive layer is controlled to be 70-160°C, and can be 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150, 155, 160, or any value between 70 and 160°C.

[0081] In the present invention, the thickness H of the insulating rubber layer is controlled, 0.02mm≤H≤0.15mm, and can be 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, or any value between 0.02mm and 0.15mm.

[0082] In the present invention, the insulating adhesive layer includes one or more adhesive films.

[0083] In some specific embodiments of the present invention, the insulating adhesive layer includes a layer of adhesive film, a layer of adhesive film and a layer of adhesive film b arranged in sequence, wherein the total thickness of the insulating adhesive layer is 0.02 to 0.12 mm, and can be 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, or any value between 0.02 mm and 0.12 mm.

[0084] Specifically, the a-layer adhesive film includes a butene polymer. In some specific embodiments of the present invention, the a-layer adhesive film includes a butene polymer and a propylene polymer. The thickness of the a-layer adhesive film is 0.005-0.04 mm, and can be 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, or any value between 0.005-0.04 mm. The melting point is 70-120° C., and can be 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, or any value between 70-120° C.

[0085] The b-layer adhesive film includes a butene polymer. In some specific embodiments of the present invention, the b-layer adhesive film includes a butene polymer and a propylene polymer. The thickness of the b-layer adhesive film is 0.005-0.04 mm, and can be 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, or any value between 0.005-0.04 mm. The melting point is 70-120° C., and can be 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, or any value between 70-120° C.

[0086] The melting points and thicknesses of the a-layer adhesive film and the b-layer adhesive film may be the same or different.

[0087] The c-layer film includes a propylene polymer and is arranged between the a-layer film and the b-layer film. The thickness of the c-layer film is 0.005-0.04 mm, and can be 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.02, 0.03, 0.04, or any value between 0.005 and 0.04 mm. The melting point of the c-layer film is 130-160°C, and can be 130, 135, 140, 145, 150, 155, 160, or any value between 130 and 160°C.

[0088] In some preferred embodiments of the present invention, the melting point of layer C of the adhesive film is 20 to 70°C higher than that of layer A of the adhesive film, and the melting point of layer C of the adhesive film is 20 to 70°C higher than that of layer B of the adhesive film, and can be 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, or any value between 20 and 70°C.

[0089] The three insulating adhesive layers include a low-melting-point adhesive layer a, a low-melting-point adhesive layer b and a high-melting-point adhesive layer c. Among them, the adhesive layers a and b can melt first to achieve pressure relief in the case of thermal runaway of the battery cell, and the high-melting-point c layer has higher impact resistance and can improve the reliability of the sealing mechanism.

[0090] In the present invention, the melting points of the a-layer film and the b-layer film are relatively low, at 70-120°C. First, it can be ensured that when the battery cell is in normal use and the battery cell temperature is lower than 70°C, the insulating adhesive layer will not melt and cause water vapor to enter the battery cell, thereby ensuring the sealing of the sealing mechanism. Secondly, the melting points of the a-layer film and the b-layer film do not exceed 120°C, which can ensure that before the battery cell reaches the temperature of thermal runaway, the a-layer film and the b-layer film have melted and opened, and the sealing mechanism can play a role in pressure relief, thereby preventing the battery cell from catching fire and exploding. The c-layer film has a relatively high melting point. The high melting point film, as the skeleton layer of the three-layer film, has a stronger ability to resist deformation.

[0091] In the present invention, the three-layer insulating adhesive layer can improve the pressure relief sensitivity of the sealing mechanism by increasing the thickness of the a-layer adhesive film and the b-layer adhesive film with lower melting points. The thickness ratio of the three-layer adhesive film, that is, the thickness ratio of the a-layer adhesive film, the c-layer adhesive film and the b-layer adhesive film is (1-3): (1-3): (1-3), which can be 1:3:1, 2:3:2, 3:1:3, 3:2:3, 2:1:2, 1:2:1, 1:1:1, or any value between (1-3): (1-3): (1-3). More preferably, the a-layer adhesive film and the b-layer adhesive of the low melting point layer account for 40% to 85% of the total thickness of the insulating adhesive layer, which can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, or any value between 40% and 85%, and the three-layer insulating adhesive film realizes pressure relief in thermal runaway of the battery cell.

[0092] In the present invention, in the DSC test, the insulating adhesive layer has a crystallization peak at 30-130° C. In some preferred embodiments of the present invention, in the DSC test, the insulating adhesive layer includes a first crystallization peak and a second crystallization peak at 30-130° C., the crystallization temperature of the first crystallization peak is 90-120° C., and the crystallization temperature of the second crystallization peak is 30-60° C.

[0093] Among them, the higher the crystallization temperature of the insulating adhesive layer, the more perfect the crystallization, and the higher the yield stress, strength, modulus and hardness of the polymer. When the crystallization temperature of the propylene polymer in the c-layer adhesive film is in the range of 90-120°C, it can have a certain modulus and strength, as well as good toughness and ductility, absorb energy when the battery cell is impacted, and ensure the reliability of the sealing mechanism. The insulating adhesive layer is compressed by the pressure of the air pressure inside the battery cell shell at high temperature. The butene polymers in the a and b layers of adhesive film have a low crystallization temperature of 30-60°C and a low degree of crystallinity, which makes the insulating adhesive layer flexible, improves the sensitivity of the pressure relief of the sealing mechanism, and can achieve pressure relief in time.

[0094] In the present invention, in order to ensure the sealing performance and safety performance, it is also necessary to control the thermal weight loss parameters of the insulating adhesive layer.

[0095] Specifically, under nitrogen atmosphere conditions, in the TG test, the insulating adhesive layer has a heating rate of 10°C / min, and when the temperature reaches 400°C, the weight loss rate of the insulating adhesive layer is less than 10%; when the temperature reaches 600°C, the weight loss rate of the insulating adhesive layer is greater than 99%.

[0096] The melting point of the three-layer insulating adhesive layer provided by the present invention needs to be controlled between 70 and 160°C, the hot pressing temperature of the sealing mechanism processing needs to reach 180 to 200°C, and the insulating adhesive layer will begin to lose weight only in the range of 400 to 600°C, which is beneficial to the processability of the insulating adhesive layer. The hot pressing window is sufficient, and the hot pressing process will not cause the insulating adhesive layer to decompose and age, affecting the sealing and reliability of the sealing mechanism.

[0097] The present invention also provides a battery cell, comprising:

[0098] A shell body, wherein the shell body is provided with a liquid injection hole;

[0099] A sealing structure covers the injection hole, the sealing structure includes a first metal sheet, a second metal sheet and an insulating adhesive layer arranged between the first metal sheet and the second metal sheet, and the insulating adhesive layer includes the insulating adhesive layer described above.

[0100] In the present invention, the battery core includes a sealing mechanism, and the sealing structure includes a first metal sheet, a second metal sheet, and an insulating adhesive layer arranged between the first metal sheet and the second metal sheet.

[0101] One side of the first metal sheet is welded to the shell of the battery cell, and the side facing away from the shell is bonded to the insulating adhesive layer, and the side of the insulating adhesive layer facing away from the first metal sheet is connected to the second metal sheet. The sealing mechanism covers the injection hole of the lithium-ion battery. When the insulating adhesive layer is at the thermal failure temperature of the battery cell, the insulating adhesive will melt and lose its viscosity with the metal sheet, releasing the pressure inside the shell.

[0102] In the present invention, the insulating adhesive layer can be bonded to the first metal sheet and the second metal sheet by hot pressing to form a sealing structure. The insulating adhesive will first reach a molten state and fit the first metal sheet and the second metal sheet, and then be connected to the first metal sheet and the second metal sheet after cooling.

[0103] In some specific embodiments of the present invention, the insulating adhesive layer includes an a-layer adhesive film, a c-layer adhesive film, and a b-layer adhesive film arranged in sequence, the a-layer adhesive film is connected to the first metal sheet, and the surface of the a-layer adhesive film close to the first metal sheet includes C element and O element, wherein the mass content ratio of C element to O element is between 95:5 and 99.8:0.2, and can be 95:5, 96:4, 97:3, 98:2, 99:1, 99.5:0.5, 99.8:0.2, or any value between 95:5 and 99.8:0.2;

[0104] The b-layer adhesive film is connected to the second metal sheet, and the b-layer adhesive film and the surface close to the second metal sheet include C element and O element, wherein the mass content ratio of C element to O element is between 90:10 and 99.8:0.2, can be between 95:5 and 99.8:0.2, can be 95:5, 96:4, 97:3, 98:2, 99:1, 99.5:0.5, 99.8:0.2, or any value between 95:5 and 99.8:0.2;

[0105] In the present invention, the contents of C and O elements are detected by scanning electron microscopy to obtain the element distribution on the surface of the a layer film and the surface of the b layer film.

[0106] Among them, the a-layer adhesive film and the b-layer adhesive film are respectively bonded to the first metal sheet and the second metal sheet. In order to ensure the adhesion between the adhesive film and the metal, the raw materials of the butene polymer and the propylene polymer are subjected to anhydride grafting modification treatment. The surface of the a-layer adhesive film and the b-layer adhesive film has O elements, and the proportion of O elements can measure the amount of anhydride grafting modification. When the C and O element ratio is between 90:10 and 99.9:0.1, it can ensure the high bonding strength between the a-layer adhesive film and the first metal sheet, and the b-layer adhesive film and the second metal sheet at room temperature. At the same time, at high temperatures, the a-layer adhesive film and the first metal sheet, and the b-layer adhesive film and the second metal sheet lose adhesion in time, and the pressure of the battery cell inflation can break the insulating adhesive layer and the first metal sheet and the second metal sheet in time to achieve pressure relief.

[0107] In addition, the present invention also needs to control the room temperature bonding force and the thermal bonding force of the sealing mechanism, wherein the room temperature bonding force of the sealing mechanism is ≥10N / mm, preferably 10-30N / mm, and can be 10, 15, 20, 25, 30, or any value between 10-30N / mm; the thermal bonding force at a temperature of 120-130°C is 0.5-5N / mm, and can be 0.5, 0.7, 1.0, 1.2, 1.5, 1.7, 2.0, 2.2, 2.5, 2.7, 3.0, 3.2, 3.5, 3.7, 4.0, 4.2, 4.5, 4.7, 5.0, or any value between 0.5-5N / mm. In the present invention, the room temperature is defined as 25±5°C.

[0108] In the present invention, the room temperature bonding force F1 ≥ 10 N / mm can ensure that the insulating rubber layer will not separate from the first metal sheet and the second metal sheet when the sealing mechanism encounters an impact, thereby ensuring the reliability of the sealing mechanism; the thermal bonding force F2 of the sealing mechanism at high temperature ≤ 5 N / mm can ensure that after the insulating layer is softened at high temperature, the air pressure in the shell can easily break open the sealing mechanism, expose the pressure relief hole in time, form a pressure relief channel, realize the pressure relief function, and ensure the safety performance of the battery.

[0109] In the present invention, the test method for the room-temperature bonding force is: at room temperature, the sealing mechanism is placed, with a push rod, through the first pressure relief hole on the first metal sheet and the second pressure relief hole on the insulating rubber layer in sequence, and the second metal sheet is pushed to separate the first metal sheet, the insulating rubber and the second metal sheet. The maximum force during the test is the room-temperature bonding force F1.

[0110] In the present invention, the test method of the thermal bonding force is: heat the sealing mechanism to 120-130°C, use a push rod to pass through the first pressure relief hole on the first metal sheet and the second pressure relief hole of the insulating glue layer in sequence, push the second metal sheet, separate the first metal sheet, the insulating glue and the second metal sheet, and the maximum force during the test is the thermal bonding force F2.

[0111] In some specific embodiments of the present invention, the materials of the first metal sheet and the second metal sheet are independently selected from one or more of nickel, nickel alloy, copper, copper-plated nickel, aluminum and aluminum alloy.

[0112] When the first metal sheet and the second metal sheet are made of one or more of nickel and its nickel alloy, it can be ensured that the metal sheet of the sealing mechanism will not be electrochemically corroded. One side of the first metal sheet is welded to the housing, and the other side is bonded to the a layer film of the insulating adhesive layer. The heat of the battery cell can be quickly transferred to the a layer film of the insulating adhesive layer through the first metal sheet.

[0113] When the first metal sheet and the second metal sheet use copper or copper-plated nickel, the heat transfer coefficient of copper is greater than that of nickel, which is conducive to the heat in the shell being transferred to the insulating rubber layer through the second metal sheet, so that the insulating rubber layer can be melted and opened faster, reducing the risk of safety problems such as explosion and fire in the shell, thereby improving the safety performance of the battery cell with the shell. Copper has poor corrosion resistance. Using a copper-plated nickel metal sheet with a coating thickness of 0.01 to 0.15 mm is not only conducive to the temperature sensitivity of the sealing mechanism to achieve pressure relief, but also can ensure the sealing of the sealing mechanism. Further, the thickness of the copper-plated nickel coating can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, or any value between 0.01 and 0.15 mm.

[0114] When the first metal sheet and the second metal sheet use one or more of aluminum and aluminum alloy, they will not be electrochemically corroded, and thus will not affect the sealing of the battery. Aluminum has a lower hardness than nickel, is easier to process, and has a lower manufacturing cost. Aluminum also has a higher heat transfer capacity than nickel, which is conducive to the timely loss of adhesion between the insulating rubber layer and the second metal sheet, thereby achieving the pressure relief function of the sealing mechanism.

[0115] In the present invention, the thickness of the first metal sheet is between 0.05 and 0.12 mm, and can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, or any value between 0.05 and 0.12 mm.

[0116] When the thickness of the first metal sheet is between 0.05 and 0.12 mm, it is not only conducive to the consistency of the temperature of the insulating adhesive layer a film with the temperature of the battery core, but also conducive to the melting of the layer a film to achieve pressure relief before the battery core fails thermally, and it is also conducive to the reliability of the welding between the first metal sheet and the shell.

[0117] The thickness ratio of the first metal sheet to the second metal sheet is between 1:(0.5-3), and can be 1:3, 1:2, 1:1, 1:0.5, or any ratio between 1:(0.5-3);

[0118] The thickness ratio of the first metal sheet to the insulating rubber layer is between (1-3):1, and can be 3:1, 2.9:1, 2.8:1, 2.7:1, 2.6:1, 2.5:1, 2.4:1, 2.3:1, 2.2:1, 2.1:1, 2:1, 1.5:1, 1:1, or any ratio between (1-3):1.

[0119] In the present invention, the sealing mechanism covers the position of the injection hole on the shell of the battery cell;

[0120] The first metal sheet is welded to the shell of the outer shell of the battery cell;

[0121] The first metal sheet is provided with a first pressure relief hole; the area of ​​the first pressure relief hole is smaller than the area of ​​the injection hole on the shell of the lithium ion battery;

[0122] The insulating rubber layer is provided with a second pressure relief hole, the area of ​​the second pressure relief hole is smaller than the area of ​​the first pressure relief hole, and along the vertical projection direction, the first pressure relief hole completely covers the second pressure relief hole.

[0123] The area of ​​the first pressure relief hole is 0.2-5 mm 2 , can be 0.2, 0.5, 1.0, 1.2, 1.4, 1.5, 1.6, 1.8, 2.0, 2.2, 2.4, 2.5, 2.6, 2.8, 3.0, 3.2, 3.4, 3.5, 3.6, 3.8, 4.0, 4.2, 4.4, 4.5, 4.6, 4.8, 5.0, or 0.2-5 mm 2 Any value in between.

[0124] The area of ​​the second pressure relief hole is 0.03~4mm 2, can be 0.03, 0.05, 0.1, 0.15, 0.2, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, or 0.03-4 mm 2 Any value in between.

[0125] The connection area between the insulating adhesive layer and the first metal sheet is 1 to 20 mm 2 , can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, or 1-20 mm 2 Any value in between.

[0126] The bonding area between the insulating adhesive layer and the first metal sheet is controlled to be 1 to 20 mm 2 , which can ensure the reliability of the insulating layer, specifically the sealing function of the insulating rubber layer, prevent water vapor from entering the battery core, and ensure that the insulating rubber layer will not separate from the first metal sheet when the sealing mechanism encounters an impact. In addition, it can also avoid that the pressure relief path of the insulating rubber layer is too long, which will reduce the sensitivity of the pressure relief of the sealing mechanism.

[0127] The area of ​​one side of the second metal sheet connected to the insulating adhesive layer is smaller than the total area of ​​the insulating adhesive layer and the second pressure relief hole, and the area of ​​one side of the second metal sheet connected to the insulating adhesive layer is larger than the area of ​​the second pressure relief hole, and the second metal sheet covers the second pressure relief hole.

[0128] In the present invention, the area of ​​the surface of the second metal sheet connected to the insulating adhesive layer is larger than the area of ​​the first pressure relief hole on the first metal sheet.

[0129] The area of ​​the second metal sheet connected to the insulating adhesive layer is 2 to 30 mm. 2 , can be 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, or 2-30 mm 2 Any value in between.

[0130] The bonding area between the second metal sheet and the insulating adhesive layer is 1 to 15 mm 2 , can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, or 1-15 mm 2 Any value in between.

[0131] The connection area between the insulating adhesive layer and the second metal sheet is controlled within 1 to 15 mm 2, which can ensure the reliability of the insulating adhesive layer, specifically the sealing function of the insulating adhesive layer, prevent water vapor from entering the battery core, and ensure that the insulating adhesive layer will not separate from the second metal sheet when the sealing mechanism encounters an impact. In addition, it can also avoid the insulating adhesive layer pressure relief path being too long, which will lead to a reduction in the sensitivity of the sealing mechanism pressure relief.

[0132] The present invention controls the bonding area between the insulating adhesive layer and the first metal sheet, and between the insulating adhesive layer and the second metal sheet, thereby ensuring the sealing effect and further shortening the length of the pressure relief path of the battery cell when thermal runaway occurs, thereby improving the sensitivity of the pressure relief of the battery cell.

[0133] The present invention has no special limitation on the specific shape of the sealing mechanism. To facilitate processing, in some specific embodiments of the present invention, the first pressure relief hole and the second pressure relief hole are circular, elliptical, square, or rectangular, preferably circular.

[0134] Furthermore, the insulating rubber layer is an insulating rubber ring sheet with an inner diameter of 0.2 to 1.4 mm and an outer diameter of 1.5 to 5 mm. Among them, the inner diameter can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, or 0.2-1.4 mm; the outer diameter can be 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, or any value between 1.5 and 5 mm. The present invention sets the inner diameter of the insulating rubber layer to be a ring with an inner diameter of 0.2 to 1.4 mm and an outer diameter of 1.5 to 5 mm. After being assembled with the first metal sheet and the second metal sheet into a sealing mechanism, the reliability of the sealing mechanism can be ensured, and at the same time, the pressure relief path of the insulating rubber layer will not be too long, resulting in untimely pressure relief.

[0135] Further, the first metal sheet is a metal annular sheet with an inner diameter of 0.8 to 1.5 mm and an outer diameter of 3 to 6 mm. The inner diameter can be 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, or any value between 0.8 and 1.5 mm, and the outer diameter can be 3, 3.2, 3.4, 3.5, 3.6, 3.8, 4.0, 4.2, 4.4, 4.5, 4.6, 4.8, 5.0, 5.2, 5.4, 5.5, 5.6, 5.8, 6.0, or any value between 3 and 6 mm.

[0136] Further, the second metal sheet is a non-porous metal disc with a diameter of 2 to 5.3 mm, which can be 2, 2.2, 2.4, 2.5, 2.6, 2.8, 3.0, 3.2, 3.4, 3.5, 3.6, 3.8, 4.0, 4.2, 4.4, 4.5, 4.6, 4.8, 5.0, 5.3, or any value between 2 and 5.3 mm.

[0137] Furthermore, the centers of the first metal sheet, the insulating adhesive layer and the second metal sheet are located on the same axis.

[0138] See also Figure 1 , Figure 1 This is a schematic structural diagram of the sealing mechanism provided by the present invention. Figure 1 In the figure, 11-shell; 111-liquid injection hole; 21-first metal sheet; 22-second metal sheet; 23-insulating rubber layer; 211-first pressure relief hole; 231-second pressure relief hole. Figure 1 The figure in the upper right part of the middle part is a partially enlarged cross-sectional view of the sealing mechanism.

[0139] In the present invention, the area of ​​the second pressure relief hole of the insulating rubber layer is smaller than the area of ​​the first pressure relief hole of the first metal sheet, and the diameter of the second pressure relief hole of the insulating rubber layer is smaller than the diameter of the first pressure relief hole, that is, the inner diameter of the insulating rubber layer is smaller than the inner diameter of the first metal sheet, which can ensure that there is overflow glue in the sealing mechanism, and the width of the overflow glue is 0.1mm≤W1≤0.5mm, which can ensure the reliability of the sealing mechanism, and at the same time ensure that the pressure relief path of the insulating rubber layer will not be too long, resulting in untimely pressure relief.

[0140] In the present invention, the diameter of the second metal sheet is less than the outer diameter of the insulating rubber layer, which can ensure that there is overflow glue in the sealing mechanism, and the overflow glue width is 0.05mm≤W2, which ensures the reliability of the sealing mechanism. The overflow glue width is 0.05mm≤W2, which can ensure the reliability of the sealing mechanism and avoid the untimely pressure relief caused by the long pressure relief path of the insulating rubber layer.

[0141] In the present invention, by setting the outer diameter of the first metal sheet to be larger than the diameter of the liquid injection hole, the first metal sheet can completely cover the liquid injection hole, thereby achieving a better sealing effect.

[0142] In the present invention, the battery cell further comprises a shell, a shell cover, an electrode assembly and an electrolyte, wherein the shell cover is arranged on the shell to form an accommodation space, and the accommodation space is used to accommodate the electrode assembly and the electrolyte.

[0143] In some specific embodiments of the present invention, the shell includes a shell bottom and a plurality of side walls surrounding the shell bottom, and the shell bottom is square, L-shaped or other special-shaped structures; preferably, the shell is a steel shell.

[0144] Preferably, the shell includes a first side wall, the injection hole is arranged on the first side wall and is connected to the accommodating space, the sealing structure covers the injection hole, and the injection hole is used to inject electrolyte into the shell during the battery cell manufacturing process. The present invention adopts a sealing mechanism to cover the injection hole, and the sealing mechanism can be used to replace the sealing plate. The injection hole can also exist as a pressure relief through hole to realize the pressure relief function. There is no need to reserve space for the pressure relief component, and the space of the shell can be fully utilized to improve the energy density.

[0145] One side of the first metal sheet of the sealing mechanism is connected to the first side wall, the side of the first metal sheet facing away from the shell is connected to the insulating rubber layer, and the side of the insulating rubber layer facing away from the first metal sheet is connected to the second metal sheet.

[0146] The electrode assembly is arranged in the shell. The electrode assembly includes a stacked positive electrode sheet, a separator, and a negative electrode sheet; the lithium-ion battery provided by the present invention also includes an electrode assembly, and the injection hole and the electrode assembly are located on the same side outer wall of the shell.

[0147] See also Figure 2 , Figure 2 The schematic diagram of the structure of the lithium-ion battery provided by the present invention: 1-shell; 2-sealing mechanism; 3-liquid injection hole; 4-positive electrode assembly; 5-negative electrode assembly.

[0148] The present invention can obtain a lithium ion battery with good sealing performance and pressure relief capacity by controlling the peak intensity ratio of the strong diffraction peak of the butene polymer in the XRD spectrum in the sealant layer. Further, by controlling the half-peak width of the strong diffraction peak of the insulating glue layer, the ratio of the absorption peak of the infrared absorption spectrum, the thermal compression deformation, the melting point, the thermal weight loss parameter, the room temperature adhesion, the thermal adhesion, the crystallization parameter, the number of layers of the insulating glue, and the material and structural parameters of each layer, the sealing performance and pressure relief capacity of the lithium ion battery can be further improved.

[0149] In order to further understand the present invention, the lithium ion battery sealing mechanism and the lithium ion battery provided by the present invention are described below in conjunction with embodiments, and the protection scope of the present invention is not limited by the following embodiments.

[0150] Preparation of the sealing mechanism used in Example 1:

[0151] Preparation of sealing mechanism: The sealing mechanism comprises a first metal sheet, a second metal sheet and an insulating adhesive layer with adhesiveness arranged between the first metal sheet and the second metal sheet;

[0152] The first metal sheet is a nickel sheet with a thickness of 0.08 mm, an inner diameter of 1 mm, and an outer diameter of 3.4 mm.

[0153] The second metal sheet is a nickel sheet with a thickness of 0.15 mm, a diameter of 2.5 mm, and an area of ​​4.9 mm. 2 .

[0154] The thickness ratio of the first metal sheet to the second metal sheet is 1:1.875.

[0155] The total thickness of the insulating rubber layer is 80 μm, the inner diameter is 0.5 mm, and the outer diameter is 2.2 mm.

[0156] The thickness ratio of the first metal sheet to the insulating adhesive layer is 1:1.

[0157] The insulating adhesive layer structure is a three-layer structure formed by a layer of adhesive film / c layer of adhesive film / b layer of adhesive film:

[0158] A layer of adhesive film: close to the first metal sheet, the main material is a mixture of polybutylene and polypropylene, the thickness is 28μm, and the melting points are 75±5℃ and 100±5℃ respectively. The a layer of adhesive film is connected to the first metal sheet, and the surface of the a layer of adhesive film close to the first metal sheet includes C element and O element, wherein the mass content ratio of C element to O element is 99.4:0.6;

[0159] C layer film: the main material is polypropylene, the thickness is 24μm, the melting point is 140±8℃;

[0160] Layer b adhesive film: The material is the same as layer a adhesive film, and is bonded to the second metal sheet, with a thickness of 28 μm, and melting points of 75±5°C and 100±5°C respectively. Layer b adhesive film is connected to the second metal sheet, and the surface of layer b adhesive film and the surface close to the second metal sheet include C element and O element, wherein the mass content ratio of C element to O element is 99.4:0.6.

[0161] The first metal sheet is a circular metal sheet. One side of the first metal sheet is welded to the steel shell, and the side away from the shell is bonded to the layer a of the insulating adhesive layer. The bonding area between the layer a and the first metal sheet is 4.5±0.2mm. 2 The first metal sheet is provided with a first pressure relief hole; the area of ​​the first pressure relief hole is smaller than the area of ​​the injection hole on the shell of the lithium-ion battery, and the area is 0.785mm 2 The insulating rubber layer is provided with a second pressure relief hole, the area of ​​the second pressure relief hole is smaller than the area of ​​the first pressure relief hole, and the area is 0.196mm 2 In addition, along the vertical projection direction, the first pressure relief hole covers the second pressure relief hole. The first pressure relief hole and the second pressure relief hole are circular, the second metal sheet is a non-porous metal circular sheet, and the bonding area between the second metal sheet and the layer B adhesive film is 4.7±0.2mm 2 The insulating adhesive layer is a circular insulating adhesive layer. The centers of the first metal sheet, the insulating adhesive layer, the second metal sheet and the injection hole are located on the same axis.

[0162] In the XRD spectrum of the insulating rubber layer, there is a first diffraction peak at a 2θ angle position of 9 to 12°, and a third diffraction peak at a 2θ angle position of 18 to 22°. The first diffraction peak and the third diffraction peak are characteristic peaks of butene polymers. There is a second diffraction peak at a 2θ angle position of 13 to 15°, and a fourth diffraction peak at a 2θ angle position of 16 to 18°. The second diffraction peak and the fourth diffraction peak are characteristic peaks of propylene polymers.

[0163] The ratio of the peak intensity of the first diffraction peak to the peak intensity of the second diffraction peak is 3:1;

[0164] The half-peak width of the first diffraction peak is 0.46°.

[0165] In the infrared absorption spectrum of the insulating adhesive layer, at a wave number 1 / λ of 1500 to 1300 cm -1 The interval includes the first absorption peak and the second absorption peak, and the wave number 1 / λ of the first absorption peak is 1378cm -1 , the wave number 1 / λ of the second absorption peak is 1460cm -1 , the ratio of the absorption intensity of the first absorption peak to that of the second absorption peak is 0.76;

[0166] In the DSC test, the insulating adhesive layer has a first crystallization peak and a second crystallization peak at 30-130°C, the crystallization temperature of the first crystallization peak is 115±5°C, and the crystallization temperature of the second crystallization peak is 45±5°C.

[0167] Under nitrogen atmosphere, in the TG test, the insulating adhesive layer has a heating rate of 10°C / min, and when the temperature reaches 400°C, the weight loss rate of the insulating adhesive layer is 0.4%; when the temperature reaches 600°C, the weight loss rate of the insulating adhesive layer is 99.65%.

[0168] At 100°C, the thermal compression deformation of the insulating adhesive layer is 17.52%.

[0169] The sealing mechanism is obtained by hot pressing and bonding the first metal sheet, the insulating adhesive layer and the second metal sheet in sequence. The normal temperature bonding force of the sealing mechanism is 20.79 N / mm, and the hot bonding force is 2.07 N / mm.

[0170] The sealing mechanism is welded to the injection hole of the steel shell body, and the injection hole is covered to obtain a battery cell.

[0171] The prepared insulating adhesive layer was subjected to XRD, infrared absorption spectrum, DSC, electron microscope observation, thermal weight loss, adhesion, and structural parameters of each layer. The results are shown in Table 1 and Figures 4-5 . Figure 4 This is the XRD detection spectrum of the insulating adhesive layer prepared in Example 1. Figure 5 This is the infrared spectrum of the insulating adhesive layer prepared in Example 1. Figure 4 Among them, 2321 and 2322 are diffraction peaks of polybutene, and 2323 and 2324 are diffraction peaks of polypropylene.

[0172] Preparation of the sealing mechanism used in Example 2:

[0173] On the basis of Example 1, the XRD peak intensity ratio of the insulating adhesive layer was changed. The ratio of the peak intensity of the first diffraction peak to the second diffraction peak was 0.5:1, and the half-peak width of the first diffraction peak was 0.62°.

[0174] In the infrared absorption spectrum of the insulating adhesive layer, the ratio of the absorption intensity of the first absorption peak to that of the second absorption peak is 0.74;

[0175] At 100°C, the thermal compression deformation of the insulating adhesive layer is 2.11%.

[0176] The room temperature bonding force of the sealing mechanism is 27.61 N / mm, and the hot bonding force is 3.83 N / mm.

[0177] Keeping other conditions unchanged, a sealing mechanism is obtained.

[0178] Preparation of the sealing mechanism used in Example 3:

[0179] On the basis of Example 1, the XRD peak intensity ratio of the insulating adhesive layer was changed. The ratio of the peak intensity of the first diffraction peak to the second diffraction peak was 1.5:1, and the half-peak width of the first diffraction peak was 0.55°.

[0180] In the infrared absorption spectrum of the insulating adhesive layer, the ratio of the absorption intensity of the first absorption peak to that of the second absorption peak is 0.74;

[0181] At 100°C, the thermal compression deformation of the insulating rubber layer is 10.11%.

[0182] The room temperature bonding force of the sealing mechanism is 22.11 N / mm, and the hot bonding force is 2.65 N / mm.

[0183] Keeping other conditions unchanged, a sealing mechanism is obtained.

[0184] Preparation of the sealing mechanism used in Example 4:

[0185] On the basis of Example 1, the XRD peak intensity ratio of the insulating adhesive layer was changed. The ratio of the peak intensity of the first diffraction peak to the second diffraction peak was 4.5:1, and the half-peak width of the first diffraction peak was 0.41°.

[0186] In the infrared absorption spectrum of the insulating adhesive layer, the ratio of the absorption intensity of the first absorption peak to the second absorption peak is 0.77;

[0187] At 100°C, the thermal compression deformation of the insulating adhesive layer is 28.8%.

[0188] The room temperature bonding force of the sealing mechanism is 19.91 N / mm, and the hot bonding force is 1.99 N / mm.

[0189] Preparation of the sealing mechanism used in Example 5:

[0190] On the basis of Example 1, the XRD peak intensity ratio of the insulating adhesive layer was changed. The ratio of the peak intensity of the first diffraction peak to the second diffraction peak was 0.75:1, and the half-peak width of the first diffraction peak was 0.34°.

[0191] In the infrared absorption spectrum of the insulating adhesive layer, the ratio of the absorption intensity of the first absorption peak to the second absorption peak is 0.91;

[0192] In the insulating adhesive layer, the thickness of the adhesive film layer a is 15 μm; the melting point is 75±5°C, 120±5°C; the content ratio of C and O elements between the adhesive film layer a and the bonding surface of the first metal sheet is 98.4:1.6;

[0193] The thickness of the b layer film is 15 μm, and the melting point is 75±5°C; 120±5°C; the content ratio of C and O elements between the b layer film and the bonding surface of the second metal sheet is 98.4:1.6;

[0194] The thickness of the c-layer film is 50 μm and the melting point is 150±8°C.

[0195] In the DSC test, the crystallization temperature of the first crystallization peak is 110±5°C, and the crystallization temperature of the second crystallization peak is 40±5°C.

[0196] Under nitrogen atmosphere, in the TG test, the insulating adhesive layer has a heating rate of 10°C / min, and when the temperature reaches 400°C, the weight loss rate of the insulating adhesive layer is 0.25%; when the temperature reaches 600°C, the weight loss rate of the insulating adhesive layer is 99.55%.

[0197] At 100°C, the thermal compression deformation of the insulating adhesive layer is 11.16%.

[0198] The room temperature bonding force of the sealing mechanism is 17.71 N / mm, and the hot bonding force is 2.68 N / mm.

[0199] Keeping other conditions unchanged, a sealing mechanism is obtained.

[0200] Preparation of the sealing mechanism used in Example 6:

[0201] On the basis of Example 1, the ratio of the peak intensity of the first diffraction peak to the second diffraction peak of the insulating adhesive layer is changed to 0.75:1, and the half-peak width of the first diffraction peak is 0.34°.

[0202] In the infrared absorption spectrum of the insulating adhesive layer, the ratio of the absorption intensity of the first absorption peak to that of the second absorption peak is 1.8;

[0203] In the insulating adhesive layer, the thickness of the adhesive film a is 15 μm; the melting point is 75±5°C, 120±5°C; the content ratio of C and O elements between the adhesive film a and the bonding surface of the first metal sheet is 98.2:1.8;

[0204] The thickness of the b layer adhesive film is 15 μm, and the melting point is 75±5°C; 120±5°C; the content ratio of C and O elements between the b layer adhesive film and the bonding surface of the second metal sheet is 98.2:1.8;

[0205] The thickness of the c-layer film is 50 μm and the melting point is 150±8°C.

[0206] In the DSC test, the crystallization temperature of the first crystallization peak is 110±5°C, and the crystallization temperature of the second crystallization peak is 40±5°C.

[0207] Under nitrogen atmosphere, in the TG test, the insulating adhesive layer has a heating rate of 10°C / min, and when the temperature reaches 400°C, the weight loss rate of the insulating adhesive layer is 0.15%; when the temperature reaches 600°C, the weight loss rate of the insulating adhesive layer is 99.55%.

[0208] At 100°C, the thermal compression deformation of the insulating adhesive layer is 13.32%.

[0209] The room temperature bonding force of the sealing mechanism is 12.71 N / mm, and the hot bonding force is 2.20 N / mm.

[0210] Keeping other conditions unchanged, a sealing mechanism is obtained.

[0211] Preparation of the sealing mechanism used in Example 7:

[0212] On the basis of Example 1, the insulating adhesive layer is changed to have a heating rate of 10°C / min in a nitrogen atmosphere during a TG test. When the temperature reaches 400°C, the weight loss rate of the insulating adhesive layer is 4.9%; when the temperature reaches 600°C, the weight loss rate of the insulating adhesive layer is 99.65%.

[0213] At 100°C, the thermal compression deformation of the insulating adhesive layer is 16.13%.

[0214] The room temperature bonding force of the sealing mechanism is 17.82N / mm, and the hot bonding force is 2.66N / mm.

[0215] Preparation of the sealing mechanism used in Example 8:

[0216] On the basis of Example 1, the insulating adhesive layer is changed to a nitrogen atmosphere in the TG test with a heating rate of 10°C / min. When the temperature reaches 400°C, the weight loss rate of the insulating adhesive layer is 9.3%; when the temperature reaches 600°C, the weight loss rate of the insulating adhesive layer is 99.65%.

[0217] At 100°C, the thermal compression deformation of the insulating adhesive layer is 14.32%.

[0218] The room temperature bonding force of the sealing mechanism is 15.95N / mm, and the hot bonding force is 2.85N / mm.

[0219] Example 9

[0220] On the basis of Example 1, the content ratio of C and O elements between the adhesive film layer a and the bonding surface of the first metal sheet is changed to 95.5:4.5;

[0221] The content ratio of C and O elements between the bonding surface of the b-layer adhesive film and the second metal sheet is 95.5:4.5;

[0222] At 100°C, the thermal compression deformation of the insulating adhesive layer is 17.31%.

[0223] The room temperature bonding force of the sealing mechanism is 37.83N / mm, and the hot bonding force is 4.40N / mm.

[0224] Example 10

[0225] On the basis of Example 1, the content ratio of C and O elements between the adhesive film layer a and the bonding surface of the first metal sheet is changed to 97.8:2.2;

[0226] The content ratio of C and O elements between the bonding surface of the b-layer adhesive film and the second metal sheet is 97.8:2.2;

[0227] At 100°C, the thermal compression deformation of the insulating adhesive layer is 16.82%.

[0228] The room temperature bonding force of the sealing mechanism is 25.19 N / mm, and the hot bonding force is 3.23 N / mm.

[0229] Embodiment 11

[0230] On the basis of Example 1, the thickness of the a layer of adhesive film is changed to 14 μm, the thickness of the b layer of adhesive film is changed to 14 μm, the thickness of the c layer of adhesive film is changed to 12 μm, the total thickness is 40 μm, and the thickness ratio of the first metal sheet to the insulating adhesive layer is 2:1.

[0231] The room temperature bonding force of the sealing mechanism is 18.26N / mm, and the hot bonding force is 1.83N / mm.

[0232] Example 12

[0233] On the basis of Example 1, the thickness of the a layer of adhesive film is changed to 10.5 μm, the thickness of the b layer of adhesive film is changed to 10.5 μm, the thickness of the c layer of adhesive film is changed to 9 μm, the total thickness is 30 μm, and the thickness ratio of the first metal sheet to the insulating adhesive layer is 2.667:1.

[0234] The room temperature bonding force of the sealing mechanism is 15.18N / mm, and the hot bonding force is 1.55N / mm.

[0235] Embodiment 13

[0236] On the basis of Example 1, the outer diameter of the insulating rubber layer is changed to 1.5 mm, the outer diameter of the first metal sheet is changed to 3.4 mm, and the diameter of the second metal sheet is changed to 1.8 mm;

[0237] The bonding area between the insulating adhesive layer and the first metal sheet is 1.45±0.05mm 2 ;

[0238] The bonding area between the second metal sheet and the insulating adhesive layer is 1.55±0.05mm 2 .

[0239] The room temperature bonding force of the sealing mechanism is 10.206 N / mm, and the hot bonding force is 0.667 N / mm.

[0240] Embodiment 14

[0241] On the basis of Example 1, the outer diameter of the insulating rubber layer is changed to 3 mm, the outer diameter of the first metal sheet is changed to 4.2 mm, and the diameter of the second metal sheet is changed to 3.3 mm;

[0242] The bonding area between the insulating adhesive layer and the first metal sheet is 7.2±0.1mm 2 ;

[0243] The bonding area between the second metal sheet and the insulating adhesive layer is 6.85±0.05mm 2 .

[0244] The room temperature bonding force of the sealing mechanism is 28.83N / mm, and the hot bonding force is 2.66N / mm.

[0245] Embodiment 15

[0246] On the basis of Example 1, the outer diameter of the insulating rubber layer is changed to 4 mm, the outer diameter of the first metal sheet is changed to 5.2 mm, and the diameter of the second metal sheet is changed to 4.3 mm;

[0247] The bonding area between the insulating adhesive layer and the first metal sheet is 13.05±0.05mm 2 ;

[0248] The bonding area between the second metal sheet and the insulating adhesive layer is 12.35±0.05mm 2 .

[0249] The room temperature bonding force of the sealing mechanism is 34.39 N / mm, and the hot bonding force is 3.88 N / mm.

[0250] Example 16

[0251] On the basis of Example 1, the material of the first metal sheet is changed to copper plated with nickel;

[0252] The room temperature bonding force of the sealing mechanism is 19.79 N / mm, and the hot bonding force is 1.91 N / mm.

[0253] Embodiment 17

[0254] Based on Example 1, the material of the second metal sheet is changed to aluminum;

[0255] The room temperature bonding force of the sealing mechanism is 18.38N / mm, and the hot bonding force is 1.97N / mm.

[0256] Embodiment 18

[0257] On the basis of Example 1, the insulating adhesive layer is changed to a single-layer structure, and the melting points are 75±5°C, 100±5°C, and 140±5°C.

[0258] At 100°C, the thermal compression deformation of the insulating adhesive layer is 15.34%.

[0259] The room temperature bonding force of the sealing mechanism is 19.72N / mm, and the hot bonding force is 2.57N / mm.

[0260] Embodiment 19

[0261] On the basis of Example 1, the thickness of the first metal sheet is changed to 0.06 mm, and the thickness ratio of the first metal sheet to the second metal sheet is 0.06:0.15=1:2.5;

[0262] The thickness of the a layer of adhesive film is 21 μm, the thickness of the b layer of adhesive film is 21 μm, the thickness of the c layer of adhesive film is 18 μm, and the total thickness is 60 μm. The thickness ratio of the first metal sheet to the insulating adhesive layer is 1:1.

[0263] The room temperature bonding force of the sealing mechanism is 20.33N / mm, and the hot bonding force is 2.07N / mm.

[0264] Embodiment 20

[0265] On the basis of Example 1, the thickness of the first metal sheet is changed to 0.12 mm, and the thickness ratio of the first metal sheet to the second metal sheet is 1:1.25;

[0266] The thickness of the a layer of adhesive film is 35 μm, the thickness of the b layer of adhesive film is 35 μm, the thickness of the c layer of adhesive film is 30 μm, and the total thickness is 100 μm. The thickness ratio of the first metal sheet to the insulating adhesive layer is 1.2:1.

[0267] The room temperature bonding force of the sealing mechanism is 20.93N / mm, and the hot bonding force is 2.12N / mm.

[0268] Embodiment 21

[0269] On the basis of Example 1, the thickness of the first metal sheet is changed to 0.16 mm, and the thickness ratio of the first metal sheet to the second metal sheet is 1:0.93;

[0270] The thickness of the a layer of adhesive film is 35 μm, the thickness of the b layer of adhesive film is 35 μm, the thickness of the c layer of adhesive film is 30 μm, and the total thickness is 100 μm. The thickness ratio of the first metal sheet to the insulating adhesive layer is 1.6:1.

[0271] The room temperature bonding force of the sealing mechanism is 21.85N / mm, and the hot bonding force is 2.03N / mm.

[0272] Embodiment 22

[0273] On the basis of Example 1, the thickness of the second metal sheet is changed to 0.1 mm, and the thickness ratio of the first metal sheet to the second metal sheet is 1:1.25;

[0274] The room temperature bonding force of the sealing mechanism is 18.12 N / mm, and the hot bonding force is 2.01 N / mm.

[0275] Embodiment 23

[0276] On the basis of Example 1, the thickness of the first metal sheet is changed to 0.05 mm, and the thickness ratio of the first metal sheet to the second metal sheet is 1:0.625;

[0277] The room temperature bonding force of the sealing mechanism is 15.78N / mm, and the hot bonding force is 2.06N / mm.

[0278] Embodiment 24

[0279] On the basis of Example 1, the XRD peak intensity ratio of the insulating adhesive layer was changed. The ratio of the peak intensity of the first diffraction peak to the second diffraction peak was 0.75:1, and the half-peak width of the first diffraction peak was 0.34°.

[0280] In the infrared absorption spectrum of the insulating adhesive layer, the ratio of the absorption intensity of the first absorption peak to the second absorption peak is 2.2;

[0281] In the insulating adhesive layer, the thickness of the adhesive film a is 15 μm; the melting point is 75±5°C, 120±5°C; the content ratio of C and O elements between the adhesive film a and the bonding surface of the first metal sheet is 98.2:1.8;

[0282] The thickness of the b layer adhesive film is 15 μm, and the melting point is 75±5°C; 120±5°C; the content ratio of C and O elements between the b layer adhesive film and the bonding surface of the second metal sheet is 98.2:1.8;

[0283] The thickness of the c-layer film is 50 μm and the melting point is 150±8°C.

[0284] In the DSC test, the crystallization temperature of the first crystallization peak is 110±5°C, and the crystallization temperature of the second crystallization peak is 40±5°C.

[0285] Under nitrogen atmosphere, in the TG test, the insulating adhesive layer has a heating rate of 10°C / min, and when the temperature reaches 400°C, the weight loss rate of the insulating adhesive layer is 0.15%; when the temperature reaches 600°C, the weight loss rate of the insulating adhesive layer is 99.55%.

[0286] At 100°C, the thermal compression deformation of the insulating adhesive layer is 15.11%.

[0287] The room temperature bonding force of the sealing mechanism is 9.95N / mm, and the hot bonding force is 1.85N / mm.

[0288] Embodiment 25

[0289] On the basis of Example 1, the insulating adhesive layer was subjected to a TG test under a nitrogen atmosphere at a heating rate of 10° C. / min. When the temperature reached 400° C., the weight loss rate of the insulating adhesive layer was 12.4%.

[0290] At 100°C, the thermal compression deformation of the insulating adhesive layer is 13.38%.

[0291] The room temperature bonding force of the sealing mechanism is 13.95 N / mm, and the hot bonding force is 2.88 N / mm.

[0292] Embodiment 26

[0293] On the basis of Example 1, the content ratio of C and O elements between the adhesive film layer a and the bonding surface of the first metal sheet is changed to 93.4:6.6;

[0294] The content ratio of C and O elements between the bonding surface of the b-layer adhesive film and the second metal sheet is 93.4:6.6;

[0295] At 100°C, the thermal compression deformation of the insulating adhesive layer is 16.57%.

[0296] The room temperature bonding force of the sealing mechanism is 43.95 N / mm, and the hot bonding force is 4.88 N / mm.

[0297] Embodiment 27

[0298] On the basis of Example 1, the thickness of the a layer of adhesive film is changed to 35 μm, the thickness of the b layer of adhesive film is changed to 35 μm, the thickness of the c layer of adhesive film is changed to 30 μm, the total thickness is changed to 100 μm, and the thickness ratio of the first metal sheet to the insulating adhesive layer is changed to 0.8:1.

[0299] The room temperature bonding force of the sealing mechanism is 18.26N / mm, and the hot bonding force is 1.83N / mm.

[0300] Embodiment 28

[0301] On the basis of Example 1, the thickness of the a layer of adhesive film is changed to 7 μm, the thickness of the b layer of adhesive film is changed to 7 μm, the thickness of the c layer of adhesive film is changed to 6 μm, the total thickness is changed to 20 μm, and the thickness ratio of the first metal sheet to the insulating adhesive layer is changed to 4:1.

[0302] The room temperature bonding force of the sealing mechanism is 12.43 N / mm, and the hot bonding force is 1.13 N / mm.

[0303] Embodiment 29

[0304] On the basis of Example 1, the melting point of the a layer of adhesive film was changed to 45±5°C, 75±5°C, and 100±5°C;

[0305] The melting point of the b-layer film is 45±5℃, 75±5℃, and 100±5℃;

[0306] At 100°C, the thermal compression deformation of the insulating adhesive layer is 23.52%.

[0307] The room temperature bonding force of the sealing mechanism is 10.43N / mm, and the hot bonding force is 1.03N / mm.

[0308] Embodiment 30

[0309] On the basis of Example 1, the outer diameter of the insulating rubber layer is changed to 4.5 mm, the outer diameter of the first metal sheet is changed to 5.7 mm, and the diameter of the second metal sheet is changed to 4.8 mm;

[0310] The bonding area between the insulating adhesive layer and the first metal sheet is 16.55±0.05mm 2 ;

[0311] The bonding area between the second metal sheet and the insulating adhesive layer is 15.75±0.05mm 2 .

[0312] The room temperature bonding force of the sealing mechanism is 38.17 N / mm, and the hot bonding force is 4.26 N / mm.

[0313] Embodiment 31

[0314] On the basis of Example 1, the outer diameter of the insulating rubber layer is changed to 5 mm, the outer diameter of the first metal sheet is changed to 6.2 mm, and the diameter of the second metal sheet is changed to 5.3 mm;

[0315] The bonding area between the insulating adhesive layer and the first metal sheet is 20.45±0.05mm 2 ;

[0316] The bonding area between the second metal sheet and the insulating adhesive layer is 19.25±0.05mm 2 .

[0317] The room temperature bonding force of the sealing mechanism is 41.95 N / mm, and the hot bonding force is 5.28 N / mm.

[0318] Comparative Example 1

[0319] On the basis of Example 1, the ratio of the peak intensity of the first diffraction peak to the second diffraction peak of the insulating adhesive layer is changed to 0.01:1, and the half-peak width of the first diffraction peak is 0.66°.

[0320] In the infrared absorption spectrum of the insulating adhesive layer, the ratio of the absorption intensity of the first absorption peak to that of the second absorption peak is 0.74;

[0321] In the insulating adhesive layer, the melting point of the a layer of adhesive film is 75±5℃; 100±5℃; 125±5℃;

[0322] The thickness of the b-layer film is 15 μm, and the melting point is 75±5℃; 100±5℃; 125±5℃;

[0323] The thickness of the c-layer film is 50 μm and the melting point is 160±8°C.

[0324] In the DSC test, the crystallization temperature of the first crystallization peak is 105±5°C, and the crystallization temperature of the second crystallization peak is 80±5°C.

[0325] At 100°C, the thermal compression deformation of the insulating rubber layer is 1.11%.

[0326] The room temperature bonding force of the sealing mechanism is 30.11 N / mm, and the hot bonding force is 5.04 N / mm.

[0327] Comparative Example 2

[0328] On the basis of Example 1, the ratio of the peak intensity of the first diffraction peak to the second diffraction peak of the insulating adhesive layer is changed to 6:1, and the half-peak width of the first diffraction peak is 0.38°.

[0329] In the infrared absorption spectrum of the insulating adhesive layer, the ratio of the absorption intensity of the first absorption peak to that of the second absorption peak is 0.78;

[0330] At 100°C, the thermal compression deformation of the insulating adhesive layer is 34.30%.

[0331] The room temperature bonding force of the sealing mechanism is 17.89 N / mm, and the hot bonding force is 1.89 N / mm.

[0332] Preparation of lithium ion batteries used in the embodiments and comparative examples:

[0333] 1) Tablet preparation: The positive electrode active material, conductive agent, binder and solvent are mixed and evenly coated on the surface of the positive electrode substrate; wherein the positive electrode substrate is aluminum foil, and the positive electrode active material is mainly lithium cobalt oxide. The mixed material is coated, dried, rolled and die-cut to obtain a positive electrode sheet; The negative electrode active material, conductive agent, binder and solvent are mixed and evenly coated on the surface of the negative electrode substrate; wherein the negative electrode substrate is copper foil, and the negative electrode active material is mainly graphite. Then the mixed material is evenly coated, dried, rolled and die-cut to obtain a negative electrode sheet;

[0334] 2) Lamination welding: The prepared positive electrode sheet, negative electrode sheet and separator are laminated simultaneously, and the separator is placed between the positive and negative electrode sheets, wherein the area of ​​the separator is greater than the area of ​​the negative electrode sheet and greater than the area of ​​the positive electrode sheet; and a laminated core is obtained;

[0335] 3) The prepared coil core is placed in a steel shell and welded; after liquid injection, aging and formation, the sealing mechanism is welded to cover the liquid injection hole of the shell. After OCV, a lithium-ion steel shell battery is obtained, and the battery cell capacity is 3400-3600mAh.

[0336] Test method:

[0337] 1) Sealing mechanism adhesion test: simulate the sealing mechanism strength test, take the prepared sealing structure, place the sealing mechanism in the test mold, use an electronic universal testing machine to perform a dry push test, the pushing speed is 30mm / min, and obtain the adhesion of the insulating glue at room temperature. Heat the mold and the sealing mechanism to 125±5℃, use a push rod to pass through the third through hole on the mold, the first pressure relief hole on the first metal sheet, and the second through hole of the insulating glue layer in sequence, and push the second metal sheet. Separate the first metal sheet, the glue film, and the second metal sheet to obtain the thermal bonding strength of the insulating glue.

[0338] See also Figure 6 , Figure 6 A sealing mechanism testing mold provided by the present invention; wherein, 31 is a push rod, 32 is an upper mold, 321 is a third through hole, 33 is a lower mold, and 331 is a fourth through hole.

[0339] Specifically, the upper mold has a third through hole, the third through hole can accommodate the push rod, and the diameter of the push rod is smaller than the diameter of the second through hole of the insulating rubber layer. The lower mold has a fourth through hole, the diameter of the fourth through hole is larger than the diameter of the second metal sheet and smaller than the diameter of the first metal sheet. When testing, the first metal sheet is in a fixed state.

[0340] The mold and the sealing mechanism are heated to 125±5°C, and the maximum force during the above process is the thermal bonding force.

[0341] 2) The hot box test method is as follows:

[0342] 4.43V-130℃ hot box test: At 45℃±3℃, discharge at 0.2C to a cut-off voltage of 3.0V, and let stand for 10min; charge at 0.5C constant current and constant voltage to a voltage of 4.43V, with a cut-off current of 0.02C, and test the voltage, internal resistance, and thickness of the fully charged state at 25℃±3℃. Put the fully charged battery into the test box, and heat the test box at a temperature rise rate of (5±2)℃ / min. When the temperature in the box reaches 130℃±2℃, keep the temperature constant for 30min. After the test is completed, observe whether the battery cell catches fire. If it catches fire, it fails, otherwise it passes.

[0343] 4.45V-130℃ hot box test: At 37℃±3℃, discharge at 0.2C to a cut-off voltage of 3.0V, and let stand for 10min; charge at 0.5C constant current and constant voltage to an upper limit voltage of 4.5V, with a cut-off current of 0.02C, and test the voltage, internal resistance, and thickness of the fully charged state at 25℃±3℃. Put the fully charged battery into the test box, and heat the test box at a temperature rise rate of (5±2)℃ / min. When the temperature in the box reaches 130℃±2℃, keep the temperature constant for 30min. After the test is completed, observe whether the battery cell catches fire. If it catches fire, it fails, otherwise it passes.

[0344] 4.45V-131℃ hot box test: At 37℃±3℃, discharge at 0.2C to a cut-off voltage of 3.0V, and let stand for 10min; charge at 0.5C constant current and constant voltage to an upper limit voltage of 4.5V, with a cut-off current of 0.02C, and test the voltage, internal resistance, and thickness of the fully charged state at 25℃±3℃. Put the fully charged battery into the test box, and heat the test box at a temperature rise rate of (5±2)℃ / min. When the temperature in the box reaches 130℃±2℃, keep the temperature constant for 30min. After the test is completed, observe whether the battery cell catches fire. If it catches fire, it fails, otherwise it passes.

[0345] 80% SOC-150℃ hot box test: At 37℃±3℃, discharge at 0.2C to a cut-off voltage of 3.0V, and let stand for 10min; charge at 0.5C constant current and constant voltage to 80% SOC, and test the voltage, internal resistance, and thickness of the fully charged state at 25℃±3℃. Put the fully charged battery into the test box, and heat the test box at a temperature rise rate of (5±2)℃ / min. When the temperature in the box reaches 1350℃±2℃, keep the temperature constant for 10min. After the test is completed, observe whether the battery cell catches fire. If it catches fire, it fails, and if it does not catch fire, it passes.

[0346] 3) Drop test

[0347] At 25℃±3℃, discharge at 0.2C to the lower limit voltage, let it stand for 10 minutes, put the battery cell in a 25℃ constant temperature box, fully charge it at 0.7C constant current, and the cut-off current is 0.02C. After fully charged, drop it within 12-24h; drop it at a height of 1.5m according to the national standard 15 times on the top sealing edge (conductor and packaging film packaging side), observe whether the battery cell leaks, and record the qualified proportion.

[0348] 4)High temperature and high humidity

[0349] At 25℃±3℃, discharge to the lower limit voltage at 0.2C, let stand for 10 minutes, place the battery in a 25℃ constant temperature box, fully charge at 0.7C constant current, cut-off current 0.02C, and after fully charged. Place the battery in an environment with a temperature of 60℃ and a humidity of 95% for 336 hours, test the voltage, internal resistance, and thickness data of the fully charged state every 72 hours, and observe whether the pressure relief mechanism leaks, and record the qualified ratio after 336 hours.

[0350] Table 1

[0351]

[0352]

[0353] As shown in Table 1, compared with Example 1, Examples 2, 3, 4 and Comparative Examples 1 and 2 have the same XRD diffraction peak position of the insulating adhesive layer; the same ratio of the thickness of the insulating adhesive layer to the first metal sheet; the same polymer type, the same layer thickness, the same melting point, and the same bonding area of ​​the insulating adhesive layer; as the peak intensity ratio of the first diffraction peak to the second diffraction peak increases, it indicates that the polybutene content increases, and the increase in polybutene content is conducive to passing the hot box, but too much polybutene reduces reliability and insufficient sealing. When the ratio of the peak intensity of the first diffraction peak to the second diffraction peak is greater than 5:1, the battery cell has a higher hot box pass rate, but the reliability of high temperature, high humidity and drop cannot be guaranteed; when the ratio of the peak intensity of the first diffraction peak to the second diffraction peak is less than 0.5:1, the battery cell is difficult to release pressure at high temperature, and the hot box pass rate is insufficient. The hot box, drop, high temperature and high humidity pass rates of Examples 1, 2, 3, and 4 are all greater than 50%. Therefore, only when the ratio of the peak intensity of the first diffraction peak to the second diffraction peak is between 0.5 and 5:1 can the battery cell have a higher hot box pass rate and reliability assurance.

[0354] Compared with Example 1, Examples 5, 6, and 24 have the same XRD diffraction peak position of the insulating adhesive layer; the same thickness ratio between the insulating adhesive layer and the first metal sheet; the same polymer type, the same melting point, and the same bonding area of ​​the insulating adhesive layer; when the absorption peak of the infrared absorption spectrum is 1378cm -1 and 1460cm -1 After the peak intensity ratio changes, the reliability and sealing of the battery cell are affected. The absorption peak of the infrared absorption spectrum is 1378cm -1 and 1460cm -1 The peak intensity ratio of the polybutene decreases, the methylene content increases, the number of methyl groups in the polybutene decreases, the impact resistance is insufficient, and the drop pass rate decreases. The hot box, drop, high temperature and high humidity pass rates of Examples 5 and 6 are all greater than 60%; the hot box pass rate of Example 24 is higher, but the drop and high temperature and high humidity reliability are insufficient. Therefore, the absorption peak of the infrared absorption spectrum is 1378cm -1 and 1460cm -1 When the peak intensity ratio is 1:(0.5~2), the battery cell still has a high hot box pass rate and a certain reliability guarantee.

[0355] Compared with Example 1, Examples 7, 8, and 25 have the same XRD diffraction peak position of the insulating adhesive layer; the same ratio of the thickness of the insulating adhesive layer to the first metal sheet; the same polymer type, the same melting point, and the same bonding area of ​​the insulating adhesive layer. With the increase of low molecular weight substances, the weight loss rate at 400°C gradually increases, the room temperature bonding force decreases, and the hot bonding force increases. When the weight loss rate at 400°C is greater than 10%, the drop pass rate is 55%. The drop, high temperature and high humidity pass rates of Examples 1, 7, and 8 are all greater than 75%. Therefore, when the weight loss rate at 400°C is between 0.01 and 10%, the battery cell can have a higher hot box pass rate and reliability guarantee.

[0356] Compared with Example 1, Examples 9, 10, and 26 have the same XRD diffraction peak position of the insulating adhesive layer; the same thickness ratio between the insulating adhesive layer and the first metal sheet; the same polymer type, the same melting point, and the same bonding area of ​​the insulating adhesive layer; when the content ratio of C and O elements on the bonding surface of the a and b layers of adhesive film and the first metal sheet is related to the medium polar groups in the insulating adhesive, when the content ratio of C and O elements is greater than 95:5, the insulating adhesive has too strong adhesion and the pressure relief sensitivity is reduced. Therefore, when the content ratio of C and O elements is between 95:5 and 99.8:0.2, the battery cell can be realized with high reliability while ensuring the safety of the battery cell.

[0357] Compared with Example 1, Examples 11, 12, 27, and 28 have the same XRD diffraction peak position of the insulating adhesive layer; the same thickness structure ratio of the insulating adhesive layer; the same polymer type, the same melting point, and the same bonding area of ​​the insulating adhesive layer; the thickness of the insulating adhesive layer is related to the size of the bonding force and airtightness. The thicker the insulating adhesive layer, the worse the airtightness, but the greater the bonding force. Therefore, reducing the thickness of the insulating adhesive layer, increasing the thickness ratio of the first metal sheet and the insulating adhesive layer, the bonding force decreases, and the drop pass rate decreases; increasing the thickness of the insulating adhesive layer will increase the risk of high temperature and high humidity failure. In summary, Examples 27 and 28 have a higher hot box pass rate, but poor reliability. Examples 1, 9, and 10 can balance the safety requirements of the hot box test and have good reliability. Therefore, when the thickness ratio of the first metal sheet to the insulating adhesive layer is between 1:1 and 3:1, the battery cell has high reliability and a certain hot box pass rate, and safety can be guaranteed.

[0358] Compared with Example 1, Examples 13, 14, 15, 30, and 31 have the same XRD diffraction peak position of the insulating adhesive layer; the same thickness of the insulating adhesive layer; the same polymer type and melting point of the insulating adhesive layer; the bonding area between the first metal sheet and the insulating adhesive layer will affect the bonding effect and pressure relief sensitivity. The larger the bonding area, the better the reliability performance such as drop, but the pressure relief capacity will be greatly reduced. When the bonding area is less than 1mm 2 When the bonding area is larger than 20mm2 During the hot box test, it is difficult to achieve pressure relief and safety cannot be guaranteed. Therefore, the bonding area between the metal sheet and the insulating adhesive layer is 1 to 20 mm. 2 Within the range, the battery cells have high reliability and a certain hot box pass rate, and safety can be guaranteed.

[0359] Compared with Example 1, Examples 16 and 17 have the same XRD diffraction peak position of the insulating adhesive layer; the same thickness of the insulating adhesive layer; under the conditions that the polymer type and melting point of the insulating adhesive layer are the same; when the material of the first metal sheet and the second metal sheet are nickel and its nickel alloy, the room temperature bonding force between the insulating adhesive layer and the metal sheet is 20.79N / mm, the thermal bonding force of the insulating adhesive layer at 120-130°C is 2.07N / mm, the hot box test pass rate of the battery cell at 4.43V-130°C is 100%, and the 4.5V-130°C and The pass rates of the 4.5V-131℃ hot box test are 100% and 95% respectively, the pass rate of the 80%SOC-150℃ hot box test is 100%, the pass rate of the drop test is 100%, and the pass rate of the high temperature and high humidity is 100%; when the first metal sheet is copper-plated nickel and the second metal sheet is nickel and its nickel alloy, the room temperature bonding force between the insulating adhesive layer and the metal sheet is 19.79N / mm, the thermal bonding force of the insulating adhesive layer at 120-130℃ is 1.91N / mm, and the battery cell is tested at 4.43V-130℃ in the hot box test. The pass rate is 100%, the pass rates of the hot box test at 4.5V-130℃ and 4.5V-131℃ are 100% and 100% respectively, the pass rate of the hot box test at 80%SOC-150℃ is 100%, the pass rate of the drop test is 90%, and the pass rate of the high temperature and high humidity is 85%; when the first metal sheet is nickel and its nickel alloy, and the second metal sheet is aluminum and its aluminum alloy, the room temperature bonding force between the insulating adhesive layer and the metal sheet is 18.38N / mm, and the thermal bonding force of the insulating adhesive layer at 120-130℃ is 1.97N / mm, the hot box test pass rate of the battery cell at 4.43V-130℃ is 100%, the hot box test pass rates of 4.5V-130℃ and 4.5V-131℃ are 100% and 95% respectively, the hot box test pass rate of 80% SOC-150℃ is 100%, the drop test pass rate is 100%, and the high temperature and high humidity pass rate is 87.5%; therefore, when the material of the first metal sheet and the second metal sheet is nickel and its nickel alloy, copper-plated nickel or aluminum and its aluminum alloy, the battery cell still has a high hot box pass rate.

[0360] Compared with Example 1, Example 18 has the same XRD diffraction peak position of the insulating adhesive layer; the thickness ratio of the insulating adhesive layer to the first metal sheet is the same; the insulating adhesive layer has the same polymer type, the same layer thickness, and the same bonding area; when the insulating adhesive is a three-layer structure, the thermal compression deformation of the insulating adhesive at 100°C is 17.52%, the room temperature bonding force between the insulating adhesive layer and the metal sheet is 20.79N / mm, the thermal bonding force of the insulating adhesive layer at 120-130°C is 2.07N / mm, the pass rate of the hot box test at 4.43V-130°C is 100%, the pass rates of the hot box tests at 4.5V-130°C and 4.5V-131°C are 100% and 95% respectively, and the SOC-1 is 80% SOC-2. The pass rate of the 50℃ hot box test is 100%, the pass rate of the drop test is 100%, and the pass rate of high temperature and high humidity is 100%; when the insulating glue is a single-layer structure, the thermal compression deformation of the insulating glue at 100℃ is 15.34%, the room temperature bonding force between the insulating glue layer and the metal sheet is 19.72N / mm, and the thermal bonding force of the insulating glue layer at 120-130℃ is 2.57N / mm. The pass rate of the hot box test of the battery cell at 4.43V-130℃ is 100%, and the pass rates of the hot box tests at 4.5V-130℃ and 4.5V-131℃ are 85% and 75% respectively. The pass rate of the 80% SOC-150℃ hot box test is 85%, the pass rate of the drop test is 85%, and the pass rate of high temperature and high humidity is 80%. When the insulating glue is a multi-layer glue structure or a single-layer glue structure, the safety and reliability of the hot box can still be taken into account.

[0361] Compared with Example 1, Examples 19, 20, 21, 22, and 23 have the same XRD diffraction peak position of the insulating adhesive layer; the same polymer type of the insulating adhesive layer, and the same bonding area; as the thickness of the first metal sheet increases, the efficiency of heat transfer from the battery body to the insulating adhesive layer decreases, and the hot box pass rate decreases. When the thickness of the first metal sheet is greater than 0.12 mm, the hot box pass rate is less than 60%. As the thickness ratio of the first metal sheet to the second metal sheet decreases, the impact on the hot box is lower, but the reliability is reduced. The increase in the thickness ratio will reduce the space utilization of the battery cell. Therefore, the thickness of the first metal sheet is preferably between 0.05 and 0.12 mm, and the thickness ratio of the first metal sheet to the second metal sheet is preferably 1: (0.5 to 3).

[0362] Compared with Example 1, Example 29 has the same position of the XRD diffraction peak of the insulating adhesive layer; the thickness ratio of the insulating adhesive layer to the first metal sheet is the same; the polymer type of the insulating adhesive layer is the same, the layer thickness is the same, and the bonding area is the same; when the ratio of the peak intensity of the first diffraction peak to the second diffraction peak is 3:1, the melting points of the insulating adhesive a and b layers are 75°C & 100°C, the thermal compression deformation of the insulating adhesive at 100°C is 17.52%, the room temperature bonding force between the insulating adhesive layer and the metal sheet is 20.79N / mm, the thermal bonding force of the insulating adhesive layer at 120-130°C is 2.07N / mm, the pass rate of the hot box test of the battery cell at 4.43V-130°C is 100%, and the pass rates of the hot box tests at 4.5V-130°C and 4.5V-131°C are 100% and 95%, respectively. The passing rate of 80% SOC-150℃ hot box test is 100%, the passing rate of drop test is 100%, and the passing rate of high temperature and high humidity is 100%; when the melting points of insulating glue a and b layers are 45℃&75℃&100℃, the thermal compression deformation of the insulating glue at 100℃ is 23.52%, the room temperature bonding force between the insulating glue layer and the metal sheet is 10.43N / mm, and the thermal bonding force of the insulating glue layer at 120-130℃ is 1.03N / mm. The passing rate of the hot box test of the battery cell at 4.43V-130℃ is 100%, and the passing rates of the hot box tests at 4.5V-130℃ and 4.5V-131℃ are 100% and 100% respectively. The passing rate of 80% SOC-150℃ hot box test is 100%, the passing rate of drop test is 50%, and the passing rate of high temperature and high humidity is 50%. When the melting point of the first layer is less than 70℃, the reliability of high temperature and high humidity and drop is difficult to guarantee. Therefore, when the melting point of the insulating adhesive layer is between 70 and 130°C, both the safety and reliability of the hot box can be taken into account.

[0363] The present invention uses three layers of insulating glue a, b, and c with different melting points. The main materials of the insulating glue a and b are polypropylene and polybutylene, which have a low melting point and high bonding strength. When the battery cell is in a high temperature environment, the insulating glue a and b melt, and the bonding strength between the insulating glue and the metal sheet decreases. By changing the inner diameter and outer diameter of the insulating glue layer, the thermal bonding strength of the insulating glue can be further reduced, the opening can be achieved, and the internal heat of the battery cell can be released in advance to prevent the battery cell from catching fire;

[0364] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An insulating adhesive layer, characterized in that: In the XRD spectrum of the insulating rubber layer, a first diffraction peak exists at a 2θ angle position of 9 to 12°, and a second diffraction peak exists at a 2θ angle position of 13 to 15°, and the ratio of the peak intensity of the first diffraction peak to the second diffraction peak is (0.5 to 5):

1.

2. The insulating adhesive layer according to claim 1, characterized in that: The half-peak width of the first diffraction peak is 0.2-2°.

3. The insulating adhesive layer according to claim 1, characterized in that: In the infrared absorption spectrum of the insulating adhesive layer, at a wave number 1 / λ of 1500 to 1300 cm -1 The interval includes a first absorption peak and a second absorption peak, and the wave number 1 / λ of the first absorption peak is 1400-1300cm -1 The wave number 1 / λ of the second absorption peak is 1500-1430 cm -1 The ratio of the absorption intensity of the first absorption peak to that of the second absorption peak is 1:(0.5-2), preferably 1:(0.6-1.5).

4. The insulating adhesive layer according to claim 1, characterized in that: In the vertical direction of the insulating adhesive layer, the insulating adhesive layer is compressed with a force of 0.1N, and the temperature of the insulating adhesive layer is increased from room temperature at 10°C / min. In the range of 40 to 100°C, the thermal compression deformation of the insulating adhesive layer is 2% to 30%, preferably 5% to 20%.

5. The insulating adhesive layer according to claim 1, characterized in that: The melting point of the insulating adhesive layer is 70-160°C; And / or the thickness of the insulating rubber layer is 0.02 mm to 0.15 mm.

6. The insulating adhesive layer according to claim 1, characterized in that: The insulating adhesive layer includes a polyolefin compound; Preferably, the polyolefin compound includes propylene polymer and butene polymer; Preferably, the propylene polymer includes one or more of polypropylene, polypropylene chloride, polyacrylic acid, polyacrylate, and polyacrylonitrile; The butene polymer includes one or more of polybutene, polychloroprene, and polybutene acid.

7. The insulating adhesive layer according to claim 1, characterized in that: The insulating adhesive layer includes one or more adhesive films.

8. The insulating adhesive layer according to claim 1, characterized in that: The insulating adhesive layer comprises an a-layer adhesive film, a c-layer adhesive film and a b-layer adhesive film which are arranged in sequence, the total thickness of the insulating adhesive layer is 0.02-0.12 mm, and the thickness ratios of the a-layer adhesive film, the c-layer adhesive film and the b-layer adhesive film are (1-3):(1-3):(1-3) in sequence; Preferably, the a-layer adhesive film comprises a butene polymer, has a thickness of 0.005 to 0.04 mm, and a melting point of 70 to 120° C.; The b-layer adhesive film includes a butene polymer, has a thickness of 0.005 to 0.04 mm, and a melting point of 70 to 120°C; The c-layer adhesive film includes an propylene polymer, has a thickness of 0.005 to 0.04 mm, and a melting point of 130 to 160°C; Preferably, the melting point of the c-layer adhesive film is 20-70° C. higher than that of the a-layer adhesive film, and the melting point of the c-layer adhesive film is 20-70° C. higher than that of the b-layer adhesive film.

9. The insulating adhesive layer according to claim 1, characterized in that: In the DSC test, the insulating adhesive layer has a crystallization peak at 30-130°C; Preferably, the insulating adhesive layer comprises a first crystallization peak and a second crystallization peak at 30-130°C, the crystallization temperature of the first crystallization peak is 90-120°C, and the crystallization temperature of the second crystallization peak is 30-60°C.

10. The insulating adhesive layer according to claim 1, characterized in that: Preferably, under nitrogen atmosphere, the insulating adhesive layer is heated in TG from 25°C at a rate of 10°C / min. When the temperature reaches 400°C, the weight loss rate of the insulating adhesive layer is less than 10%; when the temperature reaches 600°C, the weight loss rate of the insulating adhesive layer is greater than 99%.

11. A battery cell, characterized in that: include: A shell body, wherein the shell body is provided with a liquid injection hole; A sealing structure, wherein the sealing structure covers the injection hole, the sealing structure comprises a first metal sheet, a second metal sheet, and an insulating adhesive layer arranged between the first metal sheet and the second metal sheet, and the insulating adhesive layer comprises the insulating adhesive layer according to any one of claims 1 to 10.

12. The battery cell according to claim 11, characterized in that: The insulating adhesive layer comprises an a-layer adhesive film, a c-layer adhesive film and a b-layer adhesive film arranged in sequence, the a-layer adhesive film is connected to the first metal sheet, and the surface of the a-layer adhesive film close to the first metal sheet comprises C element and O element, wherein the mass content ratio of C element to O element is between 95:5 and 99.8:0.2; and / or The b-layer adhesive film is connected to the second metal sheet, and the b-layer adhesive film and the surface close to the second metal sheet include C element and O element, wherein the mass content ratio of C element to O element is between 95:5 and 99.8:0.

2.

13. The battery cell according to claim 11, characterized in that: The material of the first metal sheet includes one or more of nickel, nickel alloy, copper, copper-plated nickel, aluminum and aluminum alloy; The material of the second metal sheet includes one or more of nickel, nickel alloy, copper, copper-plated nickel, aluminum and aluminum alloy; Preferably, the copper-nickel plating comprises nickel and a copper-containing plating layer arranged on the surface of the nickel, and the thickness of the copper-containing plating layer is 0.01 to 0.15 μm; Preferably, the thickness of the first metal sheet is 0.05-0.12 mm; The thickness ratio of the first metal sheet to the second metal sheet is 1:(0.5-3); The thickness ratio of the first metal sheet to the insulating adhesive layer is (1-3):

1.

14. The battery cell according to claim 11, characterized in that: The first metal sheet is connected to the housing, and the first metal sheet is provided with a first pressure relief hole; The insulating rubber layer is provided with a second pressure relief hole.

15. The battery cell according to claim 14, characterized in that: The area of ​​the first pressure relief hole is smaller than the area of ​​the liquid injection hole; The area of ​​the second pressure relief hole is smaller than that of the first pressure relief hole, and along the vertical projection direction, the first pressure relief hole completely covers the second pressure relief hole; Preferably, the area of ​​the first pressure relief hole is 0.2-5 mm 2 The area of ​​the second pressure relief hole is 0.03~4mm 2 The connection area between the insulating adhesive layer and the first metal sheet is 1 to 20 mm 2 .

16. The battery cell according to claim 15, characterized in that: The area of ​​one side of the second metal sheet connected to the insulating adhesive layer is smaller than the total area of ​​the insulating adhesive layer and the second pressure relief hole, and the area of ​​one side of the second metal sheet connected to the insulating adhesive layer is larger than the area of ​​the second pressure relief hole, and the second metal sheet covers the second pressure relief hole; Preferably, the area of ​​the second metal sheet connected to the insulating adhesive layer is 2 to 30 mm 2 The bonding area between the second metal sheet and the insulating adhesive layer is 1 to 15 mm 2 ; Preferably, the insulating rubber layer is a ring with an inner diameter of 0.2 to 1.4 mm and an outer diameter of 1.5 to 5 mm.

17. The battery cell according to claim 11, characterized in that: The battery cell comprises a shell, a shell cover, an electrode assembly and an electrolyte, wherein the shell cover is arranged on the shell, and the electrode assembly is arranged in the shell; The electrode assembly comprises a positive electrode sheet, a separator, and a negative electrode sheet stacked in layers; Preferably, the housing is a steel shell.

18. The battery cell according to claim 17, characterized in that: The pole hole and the liquid injection hole for setting the positive pole of the electrode assembly are located on the same side wall of the shell; Preferably, the battery cell further comprises a notch, and the notch is arranged on the surface of the shell cover.

19. The battery cell according to claim 18, characterized in that: The shell includes a first side wall, the pole hole injection hole of the positive pole is arranged on the first side wall, the sealing structure covers the injection hole, one side of the first metal sheet of the sealing mechanism is connected to the first side wall, the side of the first metal sheet facing away from the shell is connected to the insulating rubber layer, and the side of the insulating rubber layer facing away from the first metal sheet is connected to the second metal sheet.

Citation Information

Cited By

  • Shell assembly of battery, battery and battery pack

    CN120453593A

  • Battery casing assembly, battery and battery pack

    CN120453593B